2015
DOI: 10.1111/1744-7941.12071
|View full text |Cite
|
Sign up to set email alerts
|

Female manager career success: the importance of individual and organizational factors in South Korea

Abstract: Our paper focuses on Asian female managers and the influence of individual and organizational factors on objective and subjective career success. We use a survey and interviews of female managers in South Korea post-1997 Asian financial crisis and pre-2008 global financial crisis. Importantly, we find male-dominated business and societal cultures stemming from the context to be crucial. The implications of our findings include the greater need to take into account the restraints on individual actions and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 74 publications
4
39
0
Order By: Relevance
“…Research on Korean women leaders (Y. Cho, Kim, et al, ; Kang & Rowley, ; J. Lee, ; Rowley, Kang, & Lim, ) has been minimal. Kang and Rowley () presented reasons (e.g., Korean society's deeply rooted gender‐role stereotypes) why the number of female managers remains low based on statistical data on the labor market.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on Korean women leaders (Y. Cho, Kim, et al, ; Kang & Rowley, ; J. Lee, ; Rowley, Kang, & Lim, ) has been minimal. Kang and Rowley () presented reasons (e.g., Korean society's deeply rooted gender‐role stereotypes) why the number of female managers remains low based on statistical data on the labor market.…”
Section: Problem Statementmentioning
confidence: 99%
“…J. Lee () showed that women executives make the most of their female leadership style being soft, communicative, and caring. In a survey of 260 female managers from 65 companies in Korea, Rowley et al () revealed that their career success was critically affected by a male dominated organizational culture. These studies show a glimpse of the state of women leaders in organizations in Korea but were limited in regards to capturing the complicated picture of their challenges and opportunities.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…). Korean society has been deeply influenced by the country's Confucian cultural tradition, so work practices and networking remain largely male‐dominated in Korean organizations (Cooke ; Rowley, Kang and Lim ).…”
Section: Korean Contextsmentioning
confidence: 99%
“…Although Korean employees prefer to work in larger companies, most Korean career changers, including job-seekers and employees, highly value a strong organizational culture, vision of leaders for people, and talent development when they are choosing between seeking a new job and remaining in their current organization (Park et al 2015). Korean society has been deeply influenced by the country's Confucian cultural tradition, so work practices and networking remain largely male-dominated in Korean organizations (Cooke 2010;Rowley, Kang and Lim 2016).…”
Section: Korean Contextsmentioning
confidence: 99%